Robert Helpmann Behind the Scenes with the Australian Ballet, 1963-1965 - Potter, Michelle 1944- (Edinburgh: Edinburgh University Press, 2016)
RESUMEN: Robert Helpmann played an influential role in the early development of the Australian Ballet as choreographer and co-artistic director. The first ballets he created for the fledgling company, The Display in 1964 and Yugen in 1965, were seen as a means by which the Australian Ballet could achieve an international profile: the Helpmann name was a powerful one. But the creative development period that brought these ballets to the stage reveals a demanding side of Helpmann's personality and approach-an uncompromising collaborative aesthetic in his dealings with his collaborators. PALABRAS CLAVE: Helpmann, collaboration, ballet librettos, ballet design, artistic direction, public relations